Dampak Pandemi COVID-19 Pada Anak - Gina Noor Djalilah (Universitas Muhammadiyah Surabaya, 2020)
AbstractCOVID-19 (Corona Virus Infection Disease 2019) is an acute infectious disease caused by avirus called SARS-CoV-2, which stands for Severe Acute Respiratory Syndrome Coronavirus-2. This disease is generally characterized by symptoms of acute respiratory infection (ARI)such as fever, cough, painful swallowing and disorders of other organs such as the heart,kidneys, digestive system, nerves, eyes, skin, ENT, and others. It can also occur withoutsymptoms at all. At first the disease was discovered in Wuhan City, Hubei Province, China atthe end of December 2019. In Indonesia the first cases of COVID-19 were reported on March2, 2020.The impact of the Pandemic on children needs special attention. Based on the causes,SARS-CoV-2 infection in children is distinguished, limited access to health services, decreasedfamily economic capacity and due to school closures or distance learning. In the short term,the impact of a pandemic can increase the number of morbidity or disease, increase themortality rate due to late diagnosis and treatment, reduce immunization coverage, and reducenutritional or nutritional compliance. Meanwhile, in the long term disease outbreaks that canbe prevented by immunization can arise, increasing the prevalence of stunted and veryunderweight children, developmental disorders, including psycho-social and mentaldevelopment and future generations with loss of the actual learning period.Keywords : COVID-19, children, impact of pandemic